Driving green technology innovation: the impacts of heterogeneous environmental regulation and digital financial inclusion - Jiao, Hongrui; Deng, Hongbing; Hu, Shengmei (Frontiers in Environmental Science, 2024)
A strong environmental regulatory framework enhances green technology innovation (GTI), which is crucial for sustainable economic growth. We construct SDM models by using panel data from 108 cities in China's Yangtze River Economic Belt (YREB) from 2010 to 2020 to investigate the effects of heterogeneous environmental regulations(ER) on GTI in local and neighboring cities. The moderating influence of digital financial inclusion(DFI) is also examined within the SDM model. Our findings reveal that: (1) Different types of ER have varying impacts on GTI. (2) Commandand-control environmental regulation (CER) hinders local GTI but promotes GTI in neighboring cities. Both market-based (MER) and public-participation environmental regulations (PER) promote GTI in both local and neighboring cities. (3) DFI positively moderates the impact of ER on GTI by providing flexible finance support to enterprises. The study concludes with policy recommendations to improve environmental regulation systems, enhance regional synergistic governance, and promote digital financial inclusion for green sustainable development.